PENGARUH PELAYANAN FISKUS TERHADAP MOTIVASI WP DIMODERASI OLEH PROGRAM CELENGAN PADJEG - Suyanto Suyanto; Pasca Putri Lopian Ayu Intansari (AKUNTANSI DEWANTARA, 2017)
This study aimed to determine the effect of fiscus services on taxpayers motivation in complying with taxation. Celengan Padjeg Programe as variables that can strengthen or weaken the effect of the fiscus services on taxpayers motivation complying with taxation.The nature of this research is descriptive research with quantitative approach and using primary data types. The scope of research in the working area KPP Pratama Wonosari, Gunungkidul, Yogyakarta. Total population is at 116 with 89 samples. The method of data analysis in this study using simple regression and the absolute difference test.The results showed that the fiscus services positive effect on taxpayers motivation shown by the value t table of 6.830 with a significance level of 0.000. Celengan Padjeg Program to strengthen the influence of the fiscus services against taxpayers motivation shown by the value t table of 2.750 with a significance level of 0.007, so that Celengan Padjeg Program is quasi moderating variable.Keyword:Â Fiscus Services, Taxpayers Motivation, Celengan Padjeg Program